The shared frameshift mutation landscape of microsatellite-unstable cancers suggests immunoediting during tumor evolution - Alexej Ballhausen; Moritz Jakob Przybilla; Michael Jendrusch; Saskia Haupt; Elisabeth Pfaffendorf; Florian Seidler; Johannes Witt; Alejandro Hernandez Sanchez; Katharina Urban; Markus Draxlbauer; Sonja Krausert; Aysel Ahadova; et al. (Nature Communications, 2020)
DNA mismatch repair (MMR)-deficient cancers with microsatellite-instability are characterized by a high load of frameshift mutation-derived neoantigens. Here, by mapping the frameshift mutation landscape and predicting the immunogenicity of the resulting peptides, the authors show evidence of immunoediting in MMR-deficient colorectal and endometrial cancers.